Calcium Hydroxide Mixed With Camphoric p-Monochlorophenol or Chlorhexidine in Delayed Tooth Replantation - Trevisan, Carolina Lunardelli [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Brandini, Daniela Atili [UNESP]; Poi, Wilson Roberto [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Vendrame Ddos Santos, Claudia Leticia [UNESP]; Saito, Celia Tomiko Hamada Matida [UNESP] (Lippincott Williams & Wilkins, 2011)
This study evaluated the repair process after delayed replantation of rat teeth, using calcium hydroxide (Ca(OH)(2)) mixed with camphorated p-monochlorophenol (CMCP), chlorhexidine 2% (CHX), or saline as temporary root canal dressing to prevent and/or control inflammatory radicular resorption. Thirty Wistar rats (Rattus norvegicus albinos) had their right upper incisor extracted, which was bench-dried for 60 minutes. The dental papilla, the enamel organ, the dental pulp, and the periodontal ligament were removed. The teeth were immersed in 2% acidulated-phosphate sodium fluoride solution for 10 minutes. The root canals were dried with absorbent paper cones and divided into 3 groups of 10 animals according to root canal dressing used: group 1: Ca(OH)(2) + saline, group 2: Ca(OH)(2) + CMCP, and group 3: Ca(OH)(2) + CHX 2%. Before replanting, the teeth sockets were irrigated with saline. Histological analysis revealed the presence of inflammatory resorption, replacement resorption, and ankylosis in all 3 groups. Statistical analysis showed a significant difference between group 3 and the other groups. The use of Ca(OH)(2) mixed with CMCP or CHX did not show an advantage over the use of Ca(OH)(2) mixed with saline in preventing and/or controlling inflammatory resorption in delayed replantation of rat teeth.
Keywords: Calcium hydroxide; chlorhexidine; root canal treatment; tooth avulsion; tooth replantation